AB0398 Efficacy of Adalimumab and Tofacitinib in Rheumatoid Arthritis: Post-Hoc Analyses from A Phase 3 Study. (15th July 2016) - van Vollenhoven, R.; Cohen, S.; Mendelsohn, A.; Bananis, E.; Fan, H.; Takiya, L.; Fleischmann, R.
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of rheumatoid arthritis (RA). In a Phase 3, 12-month (Mo) study (ORAL Standard) including RA patients (pts) on stable background methotrexate (MTX), tofacitinib and adalimumab (ADA) demonstrated significant improvements in efficacy outcomes compared with placebo (PBO). 1 Objectives: To evaluate the efficacy of tofacitinib and ADA based upon American College of Rheumatology (ACR) component scores in a post-hoc analysis of ORAL Standard. Methods: ORAL Standard (NCT00853385 ) was a randomised, multicentre, Phase 3 study investigating the efficacy of oral tofacitinib 5 and 10 mg twice daily (BID) or ADA 40 mg administered subcutaneously (SC) every two weeks vs PBO in MTX inadequate responders. All pts received background MTX. Effects of tofacitinib 5 mg BID vs ADA 40 mg SC were evaluated in exploratory, post-hoc analyses at Mo 3, 6, 9 and 12 of the proportion of pts achieving ACR 20/50/70 response as well as the change from baseline in each of the following ACR components: Health Assessment Questionnaire-Disability Index (HAQ-DI), tender and swollen joint counts (TJC and SJC), Patient's Global Assessment (PtGA), erythrocyte sedimentation rate (ESR), Physician's Global Assessment (PGA), C-reactive protein (CRP) and Pain. For ACR response rates, pts who withdrew before Mo 12 were considered non-responders from that visit onward. The normal approximation approach to binomial proportions was used to analyse the ACR response. A mixed-effect model was applied to analyse the change from baseline data. Treatment differences for tofacitinib 5 mg BID vs ADA 40 mg SC were reported along with 95% confidence intervals. All analyses were descriptive and were not adjusted for multiplicity. Results: Overall, ACR20/50/70 response rates were numerically higher for tofacitinib 5 mg BID vs ADA over the 12 mo. At Mo 6 ACR20/50/70 rates for tofacitinib were 60.6%, 38.9%, 19.7% vs 57.9%, 28.9%, 9.1%, for ADA. At Mo 12 ACR20/50/70 rates for tofacitinib were 59.6%, 43.5%, 24.9%, vs 61.4%, 38.6%, 16.8% for ADA. Comparable changes from baseline were reported for tofacitinib vs ADA in HAQ-DI, ESR, TJC, SJC, CRP, PtGA, PGA and Pain over time, with numerically higher improvements observed for tofacitinib in the majority of ACR components (Table ). Previously published safety data from this study showed that infections and infestations were the most frequent AEs reported over 12 mo in both tofacitinib and ADA treatment groups. 1 Serious infection events were more frequent in tofacitinib 5 and 10 mg BID treatment groups (3.4% and 4.0%, respectively) compared with ADA (1.5%), over 12 Mo. 1 Conclusions: These post-hoc analyses show that efficacy was generally similar in comparing tofacitinib with ADA, with numerical differences in favour of tofacitinib in some efficacy parameters. The ORAL Standard study was not designed or powered for statistical comparisons between ADA and tofacitinib. Prospective studies to investigate the effect of tofacitinib compared with ADA are under way. References: van Vollenhoven RF et al. N Engl J Med 2012; 367: 508–519. Acknowledgement: This study was sponsored by Pfizer Inc. Editorial support was provided by R Bright, PhD, of Complete Medical Communications and funded by Pfizer Inc. Disclosure of Interest: R. van Vollenhoven Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, S. Cohen Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, A. Mendelsohn Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Bananis Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, H. Fan Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Takiya Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. Fleischmann Grant/research support from: Pfizer, AbbVie, Consultant for: Pfizer, AbbVie